Performance prediction of novel high efficiency coaxial rotor configuration with dissimilar rotors - Ramanujam, R.; Abhishek (My University, 2017)
This paper proposes a novel dissimilar coaxial rotor concept with significantly reduced rotor-rotor aerodynamic interaction. The performance of the proposed concept is systematically compared with regular coaxial and conventional single rotor configurations using validated BEMT based analysis for hovering flight condition. The hover performance among different rotor configurations is compared in two different ways: 1) equivalent rotor analysis with each rotor having same blade and disc area, and 2) a baseline main rotor is chosen and the performance of different anti-torque options are compared. The equivalent rotor analysis of dissimilar coaxial rotor predicts higher power consumption for the novel concept when compared to regular coaxial and equivalent single rotor, due to high profile power. The profile power is decreased by up to 50% by reducing the RPM of the anti-torque rotor to 50% of the baseline RPM. The proposed concept with reduced RPM of anti-torque rotor is predicted to consume 10-15% less power than equivalent conventional rotor without any tail rotor. The inclusion of tail rotor power for comparison of the performance of dissimilar rotor as an anti-torque concept shows a power reduction of 7–30% when compared to a single main rotor-tail rotor configuration. The analysis also predicts 10–12% less power consumption for dissimilar coaxial rotor design, when compared to a regular coaxial rotor. Within the scope of simplified analysis performed, the proposed concept appears to be an efficient alternative to conventional tail rotor for hovering flight condition.